FEEDING BEHAVIOUR OF LOHITA GRANDIS GRAY (HETEROPTERA: LARGIDAE) - DHIMAN, S.D.; DHIMAN, S.C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
The present study deals with the feeding behaviour of L. grandis. The bug mainly feeds on seeds, decayed fruits, barks and to some extent on leaves of host plant, Trewia nudiflora and other euphorbiaceous plants The IVth and Vth instars as well as adults pick up the seeds with the help of tibia and tarsi of prothorace legs and insert the maxillary and mandibulary stylets, feed on the spot or carry the seeds to some dista places. In the absence of food, the bug adopts cannibalistic behaviour.